Leonardo da Vinci [compact disc, unabridged] - Isaacson, Walter (Audioworks, Simon & Schuster Audio, 2017)
Draws on da Vinci's notebooks as well as new discoveries about his life and work in a narrative portrait that connects the master's art to his science, demonstrating how da Vinci's genius was based on ordinary qualities, including curiosity and imagination.